Pharmacodynamic and Metabolomics Studies on the Effect of Kouyanqing Granule in the Treatment of Phenol-Induced Oral Ulcer Worsened by Sleep Deprivation - Chen, Pan; Yao, Hongliang; Su, Weiwei; Zheng, Yuying; Fan, Weiyang; Zhang, Liping; Chen, Tingting; Wu, Shuling; Zhang, Weijian; He, Yan; Yan, Zenghao; Wang, Yonggang; et al. (Frontiers in Pharmacology, 2020)
Oral ulcers are the most prevalent oral mucosal diseases occurring around the world, which have no specific treatment schemes due to related to autoimmune diseases or unknown origin. Sleep deprivation increased the risk of oral health. Kouyanqing Granule (KYQG) has been used to treat inflammatory diseases of the mouth and throat with the syndrome of hyperactivity of fire due to yin deficiency for decades in China. However, the underlying mechanisms of KYQG in treating oral ulcers are still unclear. This study aimed to investigate whether the KYQG would attenuate oral ulcer worsened by sleep deprivation and discover the preliminary mechanisms of KYQG in treating oral ulcers. Thus, we investigated the chemical profiling of KYQG via UPLC-MS analysis. Then, we combined classical pharmacological experiments with metabolomics approaches on a phenol-induced oral ulcer model in rats with sleep deprivation. A total of 79 compounds were initially identified. Our observation showed that KYQG attenuated oral ulcer worsened by sleep deprivation with significantly higher ulcer healing rate. KYQG significantly reduced the levels of 5-HT and GABA in serum, and only decrease 5-HT level in brain after phenol injured followed by sleep deprivation. KYQG significantly suppressed systemic inflammation by inhibiting TNF-α, IL-1β, IL-6, IL-18, and MCP-1. Immunohistochemical analysis revealed that KYQG inhibited the IL-6 expression in the epithelium sections of buccal mucosa tissues. KYQG also significantly decreased the levels of ACTH, CORT, IgM, and 8-OHdG in serum. Serum metabolomics analysis showed a total of 30 differential metabolites changed significantly under KYQG intervention, while metabolic pathway analysis suggested that 8 metabolic pathways were dis-regulated by the altered metabolites. KYQG attenuates oral ulcer worsened by sleep deprivation probably through the regulation of neuro-immuno-endocrine system, oxidative stress, and tryptophan metabolism. This study also provides a pilot way for research of herbal medicine formula used in addressing the challenge of an increased health risk caused by sleep deficiency.